Relationship between Technical Skills Acquired and Skills Required on Electrical Equipment Servicing among Electrical Engineering Technicians in Manufacturing Industries in Keny - Keter Amos Kiprono; Prof. Okemwa Peter; Dr. Kanyeki F. G (International Journal of Engineering and Management Research, 2020)
The research sought to investigate relationship between technical skills acquired and required on electrical equipment servicing amongelectrical engineering technicians in manufacturing industries in Kenya. Quantitative research techniques were adopted in this study. The study was conducted in Nandi and Uasin-Gishu counties in Kenya, which have 7 TVETA registered and licensed public Technical Training Institutions offering Diploma, Craft Certificate and Artisan electrical engineering courses. The target population was 96 electrical engineering trainers, 15 employees from manufacturing industries and 65 electrical engineering technician trainers. A sample size comprised of 50 electrical engineering trainers, 7 employees from manufacturing industries and 29 electrical engineering technician trainers. Questionnaire were used to collect data. The instrument was pre-tested to ensure its validity by determining the internal consistency of the research instruments. Data were analyzed using descriptive and inferential analysis. There was a positive significant relationship (r=0.408, p= 0.004 2-tailed) between the electrical engineering technician acquired training at TVET institutions and the skills required for electrical equipment servicing at manufacturing industries in Kenya. The Kenyan government through the ministry of education should ensure adequate training is carried out to achieve training relevant for the needs of the industry. KICD in collaboration with CDACC and SSACs should develop a curriculum that addresses the competence requirements and occupational standard needs of the manufacturing industries.